2021
DOI: 10.1155/2021/2182761
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a Pyroptosis-Related Long Noncoding RNA Signature Associated with Osteosarcoma Microenvironment

Abstract: Background. Osteosarcoma is the most prevalent bone cancer that affects young adults and adolescents. It is the most frequent malignancy of the bone. In spite of the fact that complete surgical resection and chemotherapy have increased the overall survival of osteosarcoma patients considerably, the prognosis remains dismal in patients with recurring and/or metastasized osteosarcoma. Thus, finding predictive biomarkers representing osteosarcoma's biological variability may result in more effective treatment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Since the external database may have the biases and limitations when compared with TCGA and GTEx, we could not extract appropriate lncRNA profile as an independent external cohort for validation. This situation is consistent with several other prior studies utilizing a similar approach ( Wu et al, 2020 ; Bu et al, 2021 ; Gao and Li, 2021 ; Qu et al, 2022 ). However, we performed the RT-qPCR to detect the expression of these signature lncRNAs, which may be recognized as an external validation.…”
Section: Discussionsupporting
confidence: 93%
“…Since the external database may have the biases and limitations when compared with TCGA and GTEx, we could not extract appropriate lncRNA profile as an independent external cohort for validation. This situation is consistent with several other prior studies utilizing a similar approach ( Wu et al, 2020 ; Bu et al, 2021 ; Gao and Li, 2021 ; Qu et al, 2022 ). However, we performed the RT-qPCR to detect the expression of these signature lncRNAs, which may be recognized as an external validation.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, another study revealed that RPARP-AS1 was an N6-methyladenosine regulator in lung adenocarcinoma (LUAD) ( 67 ). Interestingly RPARP-AS1 is also an essential lncRNA associated with pyroptosis in osteosarcoma ( 60 ). Given the multiple effects of RPARP-AS1, we performed further analysis and preliminary experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained relevant data from recent literature on lncRNA-based prognostic signatures for osteosarcoma, such as: metabolism-related nine-lncRNA signature ( 58 ), metabolism-related eight-lncRNA signature ( 59 ), and pyroptosis-related three-lncRNA signature ( 60 ). We named these three signatures as Chen signature, Gong signature, and Bu signature according to the names of the authors, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…More and more studies have recently found that pyroptosis can also be involved in the progression of osteosarcoma and may be a viable target for future osteosarcoma therapy. 167 The study also found that pyroptosis is an inflammatory form of cell death that releases specific cytokines and other immunostimulatory factors that protect mammals from pathogens. 168 As a type of regulated cell death, pyroptosis is characterized by cell swelling, lysis, and the release of many pro-inflammatory factors.…”
Section: The Role and Mechanism Of Mirnas In The Development Of Osteo...mentioning
confidence: 96%